Government policy and healthcare management: proposal of a shared decision-making model - Petrillo, Antonella; Felice, Fabio de; Vanzanella, Carmela; Crispino, Filippo; Martin, Jennifer L.; Craven, Michael P.; Morgan, Stephen P.; Pecchia, Leandro (Inderscience, 2015)
As a consequence of the current economic crisis many changes have been introduced to health systems on national levels to reduce expenditure and to introduce more cost-effective methods. Then recent developments in medical technology have led to a shift in the traditional framework of physician-patient responsibility in health care decision making. In this context, the health community urges, in any case, decision makers to ensure that all changes introduced are in accordance with Health System Values. This paper presents a new decision making platform, as a tool to facilitate shared decision making, to improve the quality and transparency of tactical and strategic decisions. This new application, based on analytic quantitative method, is a component of a wider distribute web system under development, which aims to inform the new effective health technologies supporting designers in the user need elicitation and early stage health technology assessments. A case study aiming to elicit the user needs affecting the decision of whether to adopt a new magnetic resonance imaging (MRI) is also presented.